Inventing the Almost Impossible Creating, Teaching, Funding, and Leading Radical Innovation - Carleton, Tamara; West, Shaun; Cockayne, William R. (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
Looking to pioneer scientific and technological breakthroughs that create entirely new industries? This book serves as your guide. It goes beyond patents, diving deep into the intersection of foresight, engineering, and business. Explore how teams at renowned organizations such as ARPA-E, IKEA, and H2 Green Steel create radical innovation. Through critical analysis, industry case studies, and teaching examples, an international and interdisciplinary group of scholars, practitioners, and mavericks offer practical advice for bringing visionary development to life. Whether you're seeking to invent the seemingly impossible or solve problems for which no market exists yet, this book renews the research agenda for the deliberate study of invention. It will inspire and provoke you to expand your thinking and push boundaries.
Chapter 1 Introduction to Inventing the Almost Impossible -- Chapter 2 Re:design Thinking -- Chapter 3 Inspired by DARPA: An Initial Global Comparison of Radical Innovation Government Agencies -- Chapter 4 Inventing the Future of Aviation -- Chapter 5 Creating a Work Culture for Team Innovation and Imagination -- Chapter 6 Dealing with Complexity in Uncertain Environments-Wargaming in Transition -- Chapter 7 Teaching Imagination and Future-Shaping Skills: What Do Universities Offer Students to Help Them Imagine and Invent? -- Chapter 8 Future Labs, Making the Future Tangible Today -- Chapter 9 Which Moonshot Metrics Matter?.
Keywords: Technological innovations; Science -- Study and teaching; Entrepreneurship; New business enterprises; Innovation and Technology Management; Science Education; Entrepreneurship